TEST OF AN ADDITIVE DIQUARK SPECTATOR MODEL FOR MESON-BARYON QUASI-2-BODY REACTIONS - Zralek, M; Metzger, W; Vandewalle, R; Dionisi, C; Gurtu, A; Mazzucato, M; Foster, B (1979)
An additive diquark model is proposed to relate the forward cross sections of meson-baryon quasi-two-body reactions. The model consists of a quark-diquark structure for baryons combined with additivity of quark-(di)quark amplitudes. Good agreement is found between this model, which contains only one free parameter, and a large body of experimental data for charge-exchange and strangeness-exchange meson-baryon two-body reactions. This is in contrast to the SU(6)-symmetric additive quark model which disagrees violently with the data. © 1979 The American Physical Society.